IDDF2020-ABS-0044 To evaluate the feasibility and efficacy of non-radiological test to detect post operative leak after bariatric surgery. (18th November 2020) - Gupta, Nikhil; Goel, Shubham; Gupta, Arun K; Rao, ASN
Abstract : Background: Gastrograffin study under fluoroscopic guidance is a norm after sleeve gastrectomy in most of the bariatric centres to detect the post operative leak. Shifting the patient to fluoroscopic room on post operative day one and radiation exposure are major concerns associated with this protocol. A lot of studies are available to prove the efficacy of bed side oral methylene blue test to detect anastomotic leak after esophagojejunal anastomosis. We used the same principle in our bariatric patients. Methods: This prospective, interventional study was conducted on 23 patients undergoing sleeve gastrectomy for morbid obesity at our institution. Results: All patients were haemodynamically stable on post operative day-1. There was no evidence of methylene blue in the drain in any of the patients. All patients were started oral liquids after the test. Conclusions: Routine gastrograffin study under fluoroscopic guidance in the post operative period to detect leak following sleeve gastrectomy is a cumbersome procedure and can be avoided. Oral bed side Methylene blue test is a good alternative.